Formation and evolution of new primordial open cluster groups: feedback-driven star formation - Liu, Guimei; Zhang, Yu; Zhong, Jing; Chen, Li; Meng, Xiangcun; Wu, Kai (Astronomy and astrophysics, 2025)
Context. Open cluster (OC) groups are collections of spatially close OCs originating from the same giant molecular cloud. The formation mechanism of the OC groups remains unclear due to limited sample size and data precision. Recent advances in astrometric data from the Gaia mission have provided an unprecedented opportunity to study OC groups in detail. Aims. We aim to extend the sample of OC groups and explore the formation and evolution mechanisms of the newly identified pri-mordial OC groups. We focus on the impact of stellar feedback events occurring near the OC groups and their role in triggering star formation within these groups. Methods. We identified the OC group using Gaia data by analyzing the close correlations in three-dimensional (3D) spatial, 3D velocity, and age. We conducted N-body simulations to trace the dynamical evolution of these groups and obtained the birthplace of OCs. A region where supernova (SN) explosions most likely occurred was predicted around the birthplaces of OC groups, based on the correlation between OC ages and their separation from the possible SN explosion sites. We also traced the orbits of pulsars (PSRs) using the Galactic potential model to probe their association with predicted SN explosion regions. Results. We report the detection of four OC groups. The member OCs within each group are spatially proximate and exhibit similar velocities. The age spread of these OC groups is within 30 Myr, consistent with the duration of continuous star formation events. Dynamical simulations show that these OC groups gradually disperse over time, eventually evolving into independent OCs. The inference can be made that there exist specific regions surrounding Group 1 and Group 2 where the occurrence of SN explosions is highly probable. The strong correlations between OC ages and their separation from predicted SN explosion sites reveal a notable age gradient outward from the SN explosions. Additionally, we detected three PSRs near Group 1 and 26 PSRs near Group 2, whose birthplaces align with the predicted SN explosions regions. Conclusions. The member OCs within each OC group originate from the same molecular cloud, forming through a process of sequential star formation. We propose a star formation scenario in which multiple SN explosions triggered the formation of Group 1 and Group 2. Our results support the supernova-triggered star formation process and also reinforce the hierarchical star formation model, highlighting the multi-scale interactions that drive star and open cluster formation.